Oseltamivir and S-Adenosyl-L-Methionine Combination as Effective Therapeutic Strategy for Suppression of Oxidative Damage in Lung Caused by Influenza Virus Infection in Mice - Mileva, Milka; Dimitrova, Adriana; Krastev, Dimo; Alexandrova, Albena; Tsvetanova, Elina; Georgieva, Almira; Galabov, Angel (Drug Research, 2020)
Background and objectives The pathogenesis of influenza infection is associated with two general processes in the body: (a) lung damage based on virus replication; (b) overproduction of free radicals, antioxidant deficiency, and development of oxidative stress. To attack these aspects of flu pathogenesis, we explored the combined effect of the antiviral agent oseltamivir, and s-adenosyl-l-methionine (SAM) as a precursor of the endogenous antioxidant glutathione, in mice infected with influenza virus.Methods After inoculation of albino mice with 10 MLD50 of influenza virus A/Aichi/2/68 (H3N2), oseltamivir was applied twice a day, for five days post-infection in doses of 1.25 and 2.5 mg/kg. SAM was administered once a day for 10 days, starting 5 days before infection in doses of 50, 100 and 150 mg/kg.Results Monotherapy with SAM did not influence the markers of oxidative stress in the lung. Combination of SAM 50 mg/kg and oseltamivir 2.5 mg/kg affected best the virological parameters - viral titer, protection index, and mean survival time, as well as the biochemical markers of oxidative stress.Interpretation and conclusions Combining of SAM and oseltamivir in a dose of 1/4 of optimal therapeutic could be considered as a perspective therapy of influenza viral infection.
Keywords: influenza infection; oxidative stress; antioxidant; glutathione